Method FPR Developing Students’ Speech Culture And Expressive Reading Skills (Eurasian Journal of Humanities and Social Sciences, 2025)
The progress and future of society are closely linked to the level of knowledge and spiritual maturity of the younger generation. The art of speech plays an invaluable role in shaping well-rounded individuals. Politeness is an adornment of a person, and from ancient times, our ancestors placed great emphasis on speech etiquette, teaching their children the ethics of communication from an early age. This article presents insights into methods for developing students’ speech culture and expressive reading skills